Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/anie.202001830
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Versatility of Microbial Transglutaminase Using α‐Effect Nucleophiles as Noncanonical Substrates

Abstract: The substrate promiscuity of microbial transglutaminase (mTG) has been exploited in various applications in biotechnology,inparticular for the attachment of alkylamines to glutamine-containing peptides and proteins.H ere,w e expand the substrate repertoire to include hydrazines,h ydrazides,a nd alkoxyamines,resulting in the formation of isopeptide bonds with varied susceptibilities to hydrolysis or exchange by mTG.F urthermore,w ed emonstrate that simple unsubstituted hydrazine and dihydrazides can be used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…The sequence motif enrichment of this refined methodology is more pronounced compared to the previous study demonstrating the general utility of the approach in acyl phosphate trapping. 14 As we cannot a priori exclude the capture of other electrophilic modifications such as ADP-ribosylation, 29 glutamate methylation 30 and transamidation 31 we extended our analysis to all amino acids as possible modification sites. To our surprise we obtained significant labeling at Glu, Asn and Gln which cumulated in about 6000 additional sites, foremost on Gln, in both proteomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence motif enrichment of this refined methodology is more pronounced compared to the previous study demonstrating the general utility of the approach in acyl phosphate trapping. 14 As we cannot a priori exclude the capture of other electrophilic modifications such as ADP-ribosylation, 29 glutamate methylation 30 and transamidation 31 we extended our analysis to all amino acids as possible modification sites. To our surprise we obtained significant labeling at Glu, Asn and Gln which cumulated in about 6000 additional sites, foremost on Gln, in both proteomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…19D). 295 Modification of genetically installed glutamine residues in the light or heavy chain was demonstrated with these nucleophiles with minimal modification of native glutamines observed. Furthermore, conjugation with unsubstituted hydrazine and dihydrazines facilitated introduction of bioorthogonally reactive aldehydes or ketones to produce further functionalised bioconjugates.…”
Section: Transglutaminasementioning
confidence: 97%
“…Indeed, even if mTG reacts with acyl acceptor substrates with very different chemical structures, ligands containing aromatic moieties show a higher reactivity while the presence of negatively charged groups is detrimental [75]. Recently, it has been demonstrated that mTG can catalyze the reaction also with noncanonical acyl acceptor substrates containing hydrazines, hydrazides, and alkoxyamines in place of the primary ammine (Figure 2B) [76]. These substrates lead to the formation of analogous of the isopeptide bond and they also allow the introduction of reactive groups into the sidechain of Gln residues for subsequent conjugation reactions.…”
Section: Determinants For the Site-specificity Of The Mtg-catalyzed Reactionmentioning
confidence: 99%